Ecosystem Services Related to Carbon Cycling – Modeling Present and Future Impacts in Boreal Forests - Holmberg, Maria; Aalto, Tuula; Akujärvi, Anu; Arslan, Ali Nadir; Bergström, Irina; Böttcher, Kristin; Lahtinen, Ismo; Mäkelä, Annikki; Markkanen, Tiina; Minunno, Francesco; Peltoniemi, Mikko; Rankinen, Katri; et al. (Frontiers in Plant Science, 2019)
Boreal forests provide an array of ecosystem services. They regulate climate in relation with carbon, water and nutrient fluxes. Forests provide renewable raw material, food, and recreational possibilities. Rapid climate warming projected for the boreal zone may change the provision of these services. We demonstrate model based estimates of present and future ecosystem services related to carbon cycling of boreal forests. The services were derived from biophysical variables calculated by two dynamic models. Future changes in the biophysical variables were driven by climate change scenarios obtained as results of a sample of global climate models downscaled for Finland, assuming three future pathways of radiative forcing. We introduce continuous monitoring on phenology to be used in model parametrisation through a webcam network with automated image processing features. In our analysis, climate change impacts on key boreal forest ES are both beneficial and detrimental. Our results indicate an increase in annual forest growth of about 60% and an increase in annual carbon sink of roughly 40% from the reference period (1981–2010) to the end of the century. The vegetation active period was projected to start about three weeks earlier and end ten days later by the end of the century compared to currently. We found a risk for increasing drought, and a decrease in the number of soil frost days. Our results show a considerable uncertainty in future provision of boreal forest ES.